Visualization of band offsets at few-layer MoS2/Ge heterojunction. (25th June 2021) - Goel, Neeraj; Kumar, Rahul; Kumar, Mahesh
Abstract: The visualization of band alignment for designing heterostructures between transition metal dichalcogenides and germanium plays a vital role in a deeper understanding of carrier dynamics at the heterointerface. Here, to study the band alignment across the MoS2 /Ge heterojunction, we have deposited a wafer-scale highly crystalline few atomic layers MoS2 film via a highly controllable and scalable sputtering technique coupled with a post sulfurization process in a sulfur-rich environment. The Raman and XRD spectra of as-fabricated MoS2 /Ge heterojunction expose the presence of highly crystalline few atomic layer MoS2 on top of Ge substrate. Interestingly, we found a type-II band alignment at the MoS2 /Ge heterointerface having valence band, and conduction band offset values of 0.88 and 0.21 eV, which can provide very efficient recombination through spatially confining charge carriers. The calculation of band offset parameters offers a promising way for device engineering across the MoS2 /Ge heterojunction interface. Moreover, to demonstrate the practicability of the fabricated heterostructure, we explored the suitability of our device for broadband photodetection applications.